DEVELOPMENT OF WEB-BASED SYSTEM FOR BLAST DISEASE FORECASTING IN RICE PLANTATION - Samudra, Ami Anggraini; Seminar, Kudang Boro; Widodo, Widodo (Jurnal EDik Informatika, 2019)
Rice blast disease is devastating rice disease that can cause high yield loss. Therefore, it is necessary to control its distribution. This study aimed to develop a web-based system to predict the potential probability of blast disease occurrence by combining weather variable and cultural practices factor. ANN method was used to analyze the influence of weather variables on the occurrence of blast disease and to analyze the influence of cultural practices on the occurrence of blast disease executed by decision tree method. Results of this research indicate that proper cultural practices may inhibit the development of blast disease although weather variables support the development of the disease. As conclusion, a web-based  system has been developed and can be used to predict the potential probability of blast occurrence. This system can also be used as an early warning system so that users can prevent the occurrence of blast disease.